Speaking Truth or Power? Issues in Translation of South African Children’s Picture Books - Jade Smith; Ralph Adendorff (African Journal of Inter-Multidisciplinary Studies)
Children’s books communicate responsibilities and obligations such as good manners or how to overcome personal challenges. Through these stories, children learn how their society expects them to look and behave. Using a sample of bilingual picture books from the Nal’ibali reading campaign in South Africa, this research investigates the naturalised meanings projected to young readers by English stories and their Afrikaans translations. The visual symmetry of the English and Afrikaans versions of the story on a page may lead readers to think that these are direct translations or that the children are accessing similar meanings. The research questions ask whether the English readers are exposed to the same norms as the Afrikaans readers. Using a systemic functional linguistic framework to code evaluations of the books’ characters, we foreground the differences in interpersonal meaning between the English and Afrikaans translations and why these are ideologically significant. Findings show that the Afrikaans translations prioritise a young girl’s looks above her creativity, but they also construe a dedicated father who spends time with his child. Despite the small corpus, these preliminary findings indicate a need for a wider study of translation in children’s books to investigate the congruency of their translations.